Solving Equations with Brackets

Easy

Medium

Difficult

Q1) \(2(z -7) = 4 \)
Q1) 3(5y -5) = 60
Q1) 3(4z -8) = 60
Q2) \(9(x + 9) = 171 \)
Q2) 2(6z -6) = 60
Q2) 19(2y -7) = 57
Q3) \(7(y -8) = 7 \)
Q3) 2(2y + 6) = 48
Q3) 2(3z -7) = 28
Q4) \(7(w -6) = 7 \)
Q4) 8(5w -6) = 32
Q4) 2(4y + 8) = 56
Q5) \(2(w -4) = 12 \)
Q5) 6(4y -5) = 90
Q5) 11(3x -6) = 66
Q6) \(6(w + 9) = 108 \)
Q6) 3(3x + 2) = 60
Q6) 13(2y -10) = -78
Q7) \(8(z + 8) = 120 \)
Q7) 3(2x -2) = 18
Q7) 2(2w + 3) = 26
Q8) \(9(w + 5) = 99 \)
Q8) 4(3x + 9) = 84
Q8) 4(8w -4) = 80
Q9) \(9(y + 3) = 117 \)
Q9) 2(5y -7) = 86
Q9) 2(5w + 6) = 72
Q10) \(5(z + 5) = 35 \)
Q10) 4(2x -8) = 32
Q10) 9(5y -2) = 72